Immune response of heifers against a Staphylococcus aureus CP5 whole cell vaccine formulated with ISCOMATRIX™ adjuvant - Camussone, Cecilia (2013)
The shortcomings of Staphylococcus aureus vaccines to control bovine mastitis have been attributed to insufficient capacity of the vaccines to induce opsonizing antibodies and to stimulate cellular immune responses. Types of antigen, administration route and adjuvant used in a vaccine formulation have been identified as critical factors for the development of opsonic antibodies. Current commercially available vaccines for Staph. aureus bovine mastitis control are formulated with Al(OH)3 and oil-based adjuvants. The aim of this study was to evaluate the immune response of heifers immunized with a Staph. aureus CP5 whole cell vaccine formulated either with Al(OH)3 or ISCOMATRIX™. Twenty primigravid Holstein dairy heifers in the last trimester of gestation were immunized either with a vaccine formulated with ISCOMATRIX™ (n = 6), Al(OH)3 (n = 7), or saline solution (placebo) (n = 7). Immunization was carried out 38 and 10 d before calving. Heifers vaccinated with Staph. aureus adjuvanted with ISCOMATRIX™ responded with significantly higher levels of anti-bacterin and anti-CP5 IgG and IgG2 in sera than animals in the Al(OH)3 or control groups. Animals in the ISCOMATRIX™ group responded with significantly higher anti-bacterin specific IgG in whey than animals in the Al(OH)3 and control groups, detected from the first week post calving until 60 d of lactation. Sera from animals inoculated with Staph. aureus in ISCOMATRIX™, obtained 7 d post partum, significantly increased both the number of neutrophils ingesting bacteria and the number of bacteria being ingested by the neutrophils, compared with sera obtained from heifers vaccinated with Al(OH)3 or non-vaccinated controls. These features coupled to safety of the ISCOMATRIX™ formulation, warrant additional studies.